2011
DOI: 10.1088/0004-637x/743/2/183
|View full text |Cite
|
Sign up to set email alerts
|

THE X-RAY COUNTERPART OF THE HIGH-BPULSAR PSR J0726–2612

Abstract: Middle-aged, cooling neutron stars are observed both as relatively rapidly spinning radio pulsars and as more slowly spinning, strongly magnetized isolated neutron stars (INSs), which stand out by their thermal X-ray spectra. The difference between the two classes may be that the INSs initially had much stronger magnetic fields, which decayed. To test this, we used the Chandra X-ray Observatory to observe 1RXS J072559.8−261229, a possible X-ray counterpart to PSR J0726−2612, which, with its 3.44 s period and 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Its timing parameters (Table 1) are in the range of those of the XDINSs. The similarity with the XDINSs was reinforced by X-ray observations with the Chandra satellite (Speagle et al 2011), that revealed a soft thermal spectrum with blackbody temperature kT ≈ 87 eV, and pulsations with a sinusoidal, double-peaked profile. The distance of PSR J0726−2612 is unknown.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Its timing parameters (Table 1) are in the range of those of the XDINSs. The similarity with the XDINSs was reinforced by X-ray observations with the Chandra satellite (Speagle et al 2011), that revealed a soft thermal spectrum with blackbody temperature kT ≈ 87 eV, and pulsations with a sinusoidal, double-peaked profile. The distance of PSR J0726−2612 is unknown.…”
Section: Introductionmentioning
confidence: 56%
“…Pulse profile of PSR J0726−2612 in the energy range 0.15−1.5 keV obtained by folding the EPIC-pn data in 20 phase bins at the period derived from the radio ephemeris (Table 1). The vertical red line represents the location of the radio pulse (derived from Speagle et al 2011), with its uncertainty (1σ). The colored bands indicate the intervals used for the phase-resolved spectroscopy.…”
Section: Timing Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis of light curves in different energy bands and phase resolved spectroscopic study (Schwope et al 2007;Hambaryan et al 2011) provided additional confirmation on a plausibility of the model of RBS 1223 with emergent emission dominated by two emitting areas with slightly different parameters. Yet another case, Speagle et al (2011) noted that without the radio period, they might have actually identified the pulse period of PSR J0726 as half of the true value. Cropper et al (2001) performed spin pulse profile analysis of RX J0720.4−3125 based on earlier XMM-Newton observations, also folded photon arrival times with twice of the detected period via Fourier periodogram which produced a double-humped light curve with different count rates at the different peak; however, having no indication of subharmonics in the periodogram, they did not really consider twice of the period as a true one.…”
Section: Fittedmentioning
confidence: 99%
“…In spite of many searches and interesting case studies, no other thermally emitting INS, presenting exactly the same characteristics as the M7, has been identified outside the solar vicinity to date (see also the case of the high-B radio pulsar PSR J0726-2612, which is another likely product of the Gould Belt; Speagle et al 2011). It is therefore very important for population studies to understand why there are so many thermally emitting sources with similar periods (and presumably ages and magnetic fields) in such a small volume.…”
Section: Future Prospectsmentioning
confidence: 99%